Deskbound : standing up to a sitting world - Starrett, Kelly; Starrett, Juliet; Cordoza, Glen (Victory Belt Publishing, 2016)
As recent studies show that too much sitting can wreak havoc on your health, a physical therapist and best-selling author provide creative solutions for reducing the amount of time sitting and strategies for the workplace and school that will improve productivity and overall health.